PENGARUH PERILAKU PEMIMPIN TERHADAP UPAYA PEMBERDAYAAN KARYAWAN (Suatu Kajian Terhadap Pengurus Koperasi Pegawai Republik Indonesia (KPRI) Kabupaten Jember) - Sri Wahyuni (JURNAL PENDIDIKAN EKONOMI: Jurnal Ilmiah Ilmu Pendidikan, Ilmu Ekonomi dan Ilmu Sosial, 2016)
This study is based on the assumption that the staffare human resources with power, potential, and capability.However, not all the staff have the ability to optimize their powerto yield the best performancein the organization. Therefore, theattempt of the leaders to empower his staff is needed to makeproduce more creative, innovative, independent and responsiblestaff to support the enchancement of the corporate competitivepotential. The empowerement attempt is enfluenced by thebehavior orientation by the leader. Te problems raised in this study are : what is leader’s behavior like at the KPRI in the Jember Regency?; to what extent does the leader’s behavior influence the staff empowerement attempts at the KPRI in the Jember Regency?; which leader’s behavior type has the most profound influence on the staff empowerement attemps at the KPRI in the Jember Regency?.The main technique used in the data collection was by questionnaire. The data analyzed by descriptive analytical, correlation and multiple regression techniques.The findings of the study indicate that 87,10% the leaders at the KPRI in the Jember Regency implement the task-and-relationship oriented behavior. Most of the of the leaders at the KPRI in the Jember Regency (87,10%) showed high staff empowerement attempts. The multiple regression analysis shows that simultaneously, there was significant influence of the leaders with task-oriented behavior andthose with realionship-oriented behavior on the staffempowerement attempt at the KPRI in the Jember Regency (R =0,8983 ; F = 58, 57416; F Significance = 0,0000). The partial regression coefficient for the task-oriented behavior of the leaders was 0,276402 where as that for variable the relationship-oriented behavior was 1,625408. The contributing influence was 80,71%, and the remaining 19,29% was contributed by the variables outside the investigation. The leaders relationship-oriented bahavior contributed higher influence than the task-oriented one on the staff empowerement attempts at the KPRI in the Jember Regency. In short, the leaders is relationship-oriented behavior had the most profound influence on the staff empowerement attempts at the KPRI in the Jember Regency.Keyword : Leaders Behavior, Staff Empowerement